2012
DOI: 10.1097/ta.0b013e318259924c
|View full text |Cite
|
Sign up to set email alerts
|

Who should we feed? A Western Trauma Association multi-institutional study of enteral nutrition in the open abdomen after injury

Abstract: EN in the open abdomen after injury is feasible. For patients without a bowel injury, EN in the open abdomen is associated with increased fascial closure rates, decreased complication rates, and decreased mortality. EN should be initiated in these patients once resuscitation is completed. Although EN for patients with bowel injuries did not seem to affect the outcome in this study,prospective randomized controlled trials would further clarify the role of EN in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 12 publications
0
43
0
2
Order By: Relevance
“…After appropriate statistical control for severity of illness, patients who received EN before the fi rst attempt at abdominal closure experienced: significantly reduced times to defi nitive fascial closure; a signifi cant reduction in other major complications and a signifi cant reduction in mortality [ 37 ]. Although there are no randomised controlled trials with a focus on this patient group, the promising results of this large observational study demonstrate that early EN is safe, and that potential benefi ts are meaningful to patients.…”
Section: Patients Managed With An Open Abdomen After Major Surgerymentioning
confidence: 74%
“…After appropriate statistical control for severity of illness, patients who received EN before the fi rst attempt at abdominal closure experienced: significantly reduced times to defi nitive fascial closure; a signifi cant reduction in other major complications and a signifi cant reduction in mortality [ 37 ]. Although there are no randomised controlled trials with a focus on this patient group, the promising results of this large observational study demonstrate that early EN is safe, and that potential benefi ts are meaningful to patients.…”
Section: Patients Managed With An Open Abdomen After Major Surgerymentioning
confidence: 74%
“…31 Other investigators have previously shown that early enteral feeding in patients with an open abdomen can shorten the time needed to close fascia primarily and potentially decrease fistula rates as well. [12][13][14] Our group follows this approach, and we use early post-damage-control laparotomy enteral nutrition in patients without major bowel injury. We often use prealbumin as a marker for nutritional status (Table 3); however, we do recognize the limitations of prealbumin as a nutritional marker in the face of critically stressed patients, although it provided a rudimentary baseline measure of the nutritional status in both populations.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize and implement early enteral nutrition in all of our patients without bowel injury, as evidence supports the benefits of early enteral nutrition in patients with open abdomen in terms of early fascial closure and decreased fistula formation. [12][13][14] If primary closure was unsuccessful, patients were returned to the operating room every 48 to 72 hours for abdominal washout and change of the negative-pressure dressing. Intravenous fluids were limited and often diuresis was used to return a patient's weight to within 5 kg of his or her near dry weight.…”
Section: Acute Patient Populationmentioning
confidence: 99%
“…14,15 In case of patients treated by OA method, the advantages of the introduction of enteral nutrition between the 36th hour and the 4th day after the laparotomy (regardless the stage of fascial closure) were proved, but the scope of the performed operation and the stage of dysfunction of gastrointestinal tract were also considered. [16][17][18] The above-mentioned beneficial effect is observed only at the supply of 20% of daily energy requirement (the so-called trophic nutrition). So despite the fact that in the described case enteral nutrition in the early postoperative period was risky and caused the development of cachexia due to gastrointestinal insufficiency, it is recommended to introduce enteral nutrition as soon as possible, once the appropriate tolerance was gained.…”
Section: Discussionmentioning
confidence: 99%